Can founders’ dual roles facilitate innovation? – from the perspective of founders’ R&D network characteristics - Jiang, Yanhui; Wang, Danping; Zeng, Qianfang (Journal of Business Economics and Management, 2021)
Founders are crucial for the start-ups, which in turn makes it very important to study how founders’ behaviour affects the development of the start-ups. Based on the data of the companies listed on Growth Enterprise Market (GEM) and Small & Medium Enterprise (SME) board from 2014 to 2017 in China, this paper explores the impact of founders’ dual roles of R&D and management on enterprises’ innovation performance from the perspective of founders’ R&D network characteristics. The empirical research reveals that the more an enterprise’s founders participate in the R&D activities and the more central they are in the R&D network, the better the enterprise’s technological innovation performance. It is because the high network centrality enables founders the stronger ability of innovation and opportunity identification and draws their attention to innovation. This research further discloses that the promotion effect is restrained when enterprises obtain more government subsidies and founders have more power. Italso finds that founders’ R&D role does not transform the innovation output into enterprises’ value effectively though the role increases the innovation output, instead, it even restrains the transformation.